2016
DOI: 10.1002/ptr.5585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Embelin Against Lipopolysaccharide‐induced Sickness Behaviour in Mice

Abstract: Sickness behaviour is a coordinated set of adaptive behavioural changes that develop in ill individuals during the course of an infection. It is relevant to understanding depression and some aspects of the suffering that in cancer. Embelin has been reported to possess antiinflammatory, neuroprotective and anxiolytic assets and has been shown to inhibit nuclear factor κB pathway and cytokine production. The present study was undertaken to investigate the effect of embelin isolated from Embelia ribes Burm in lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Dexamethasone acts by suppressing the production of inflammatory cytokines and vasoactive substances in the initial phase of the inflammatory process [24, 29]. Dexamethasone administration in rats infected with E. coli induced a significant reduction in immobility time in the FST [24] and prevented the increased immobility time in the LPS-induced FST [26, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone acts by suppressing the production of inflammatory cytokines and vasoactive substances in the initial phase of the inflammatory process [24, 29]. Dexamethasone administration in rats infected with E. coli induced a significant reduction in immobility time in the FST [24] and prevented the increased immobility time in the LPS-induced FST [26, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Food and water intake test, pre-treatment of LPS-challenged mice with embelin (10 and 20 mg/kg) and dexamethasone (1 mg/kg) significantly reversed LPS-induced anorexia and adipsia in comparison to animals with LPS-alone-treated group. This all comparative finding eventually concluded that embelin is neuroprotective against LPS-induced sickness behavior in mice (Shaikh et al, 2016 ).…”
Section: Resultsmentioning
confidence: 86%
“…Few characteristics of the behavioral pattern including malaise, hyperalgesia, pyrexia, listlessness, and disinterest in social interactions with the environment, lethargy, behavioral inhibition, exploration and grooming, reduction of reproductive performance, anorexia and weight loss, failure to concentrate, and anxiety (Maes et al, 2012 ). The effect of embelin was evaluated in sickness behavior in mice by Shaikh et al ( 2016 ). Adult male Swiss albino mice were pre-treated with embelin (10 and 20 mg/kg per oral) for 3 days and then challenged with lipopolysaccharide (LPS; 400 μg/kg intraperitoneal).…”
Section: Resultsmentioning
confidence: 99%
“…Biomolecules 2021, 11, x 2 of 14 therefore, it is highly susceptible to oxidative damage [4][5][6]. Additionally, LPS results in behavioural abnormalities such as cognitive abnormalities and dementia [1,2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, oxidative stress-mediated pathology results when levels of peroxides and ROS exceed endogenous antioxidant defence [ 1 , 2 ]. Lipid peroxidation targets polyunsaturated fatty acids in the brain [ 4 , 5 ]. Moreover, the brain has few antioxidant defence mechanisms, therefore, it is highly susceptible to oxidative damage [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%